Transcatheter Aortic Valve Replacement in Patients With Small Aortic Annulus: An Observational Study - Hanad Bashir, MD; Christian W. Schmidt, MS; Kofi Ansah, MD; Gustavo Mendez-Hirata, MD; Geoffrey A. Answini, MD; J. Michael Smith, MD; Saad Hasan, MD; Jeffrey Griffin, MD; Robert Dowling, MD; Dean J. Kereiakes, MD; Puvi Seshiah, MD; Joseph Choo, MD; et al. (Structural Heart)
Background: The Small Annuli Randomized to Evolut or SAPIEN Trial showed superior hemodynamics of self-expanding valves (SEVs) over balloon-expandable valves (BEVs) in patients with small aortic annuli (SAA). The long-term clinical implications of these hemodynamic differences are unknown. Methods: We conducted an observational cohort study of patients with SAA, defined as an aortic valve annular area ≤430 mm2 on cardiac computed tomography, who underwent transcatheter aortic valve replacement using BEV or SEV at a single institution between August 2013 and February 2021. Patients undergoing valve-in-valve procedures or alternative access were excluded. Patient-prosthesis mismatch (PPM) was defined as moderate when indexed effective orifice area of 0.65-0.85 cm2/m2 and severe when indexed effective orifice area was <0.65 cm2/m2 (or <0.55 cm2/m2 for body mass index >30 kg/m2). The primary outcome of the study was mortality and major adverse cardiovascular events. Results: A total of 258 patients were included. The majority were female (81%) with intermediate surgical risk (median STS risk score 4.23); 90 patients (35%) received a BEV (median age 80 years [73, 86]) and 168 (65%) received a SEV (81 years [75, 85], p = 0.699). Comorbidities and risk profiles were well balanced between groups. At 30 days post-transcatheter aortic valve replacement, SEV had lower aortic valve mean gradients (8 mmHg [6, 11] vs. BEV 14 mmHg [10, 18], p < 0.001), lower peak velocities (1.86 m/s [1.60, 2.34] vs. BEV 2.52 m/s [2.14, 2.90], p < 0.001), and were less likely to have PPM (SEV 18% vs. BEV 42% (p < 0.001). At 3 years, both groups had similar mortality (SEV 23% vs. BEV 22%, p = 0.875). PPM was not associated with long-term mortality. Conclusions: In patients with SAA, we observed no difference in mortality between SEV and BEV up to 3 years after the index procedure, despite early differences in valve hemodynamics.